(untitled) (New York, 2006)
This book constitutes the thoroughly refereed post-proceedings of the 6th International Workshop on Multi-Agent-Based Simulation, MABS 2005, held in Utrecht, The Netherlands in July 2005 as an associated event of AAMAS 2005, the main international conference on autonomous agents and multi-agent systems. The 12 revised full papers presented together with 1 invited talk were carefully reviewed and selected from 28 submissions during two rounds of reviewing and improvement. The papers are organized in topical sections on coalition emergence, theories and models, applications, and environments.
Keywords: Intelligent agents (Computer software),Computer simulation,Sự mô phỏng máy tính